Medical-Grade Honey as a Potential New Therapy for Bacterial Vaginosis - Céline M. J. G. Lardenoije; Senna J. J. M. van Riel; Linsey J. F. Peters; Martine M. L. H. Wassen; Niels A. J. Cremers (MDPI AG, 2024)
The prevalence of bacterial vaginosis (BV) among women of reproductive age is 29%. BV arises from a vaginal imbalance marked by reduced levels of lactic acid-producing lactobacilli and an overgrowth of pathogenic anaerobes. The multifactorial nature of BV's pathogenesis complicates its treatment. Current antibiotic therapy exhibits a recurrence rate of about 60% within a year. Recurrence can be caused by antibiotic treatment failure (e.g., due to antimicrobial resistance), the persistence of residual infections (e.g., due to biofilm formation), and re-infection. Because of the high recurrence rates, alternative therapies are required. Medical-grade honey (MGH), known for its antimicrobial and wound healing properties in wound care, emerges as a potential novel therapy for BV. MGH exerts broad-spectrum antimicrobial activity, employing multiple mechanisms to eliminate the risk of resistance. For example, the low pH of MGH and the production of hydrogen peroxide benefit the microbiota and helps restore the natural vaginal balance. This is supported by in vitro studies demonstrating that MGH has an antibacterial effect on several pathogenic bacteria involved in the pathophysiology of BV, while lactobacilli and the vaginal microenvironment can be positively affected. In contrast to antibiotics, MGH exerts anti-biofilm activity, affects the microbiome as pre- and probiotic, and modulates the vaginal microenvironment through its anti-inflammatory, anti-oxidative, physicochemical, and immunomodulatory properties. More clinical research is required to confirm the positive effect of MGH on BV and to investigate the long-term cure rate.